2003
DOI: 10.1063/1.1539544
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence polarization of ordered GaInP/InP islands

Abstract: Room-temperature blue-green emission from InGaN/GaN quantum dots made by strain-induced islanding growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Notably, domains of ordered GaInP are formed during the overgrowth, having a double periodicity in the ͓1 11͔ and ͓11 1͔ directions. 23 The QD-induced ordering for this particular material system has recently been discussed in detail in Refs. 16 and 23. There is a rather complex interplay between the QD-QD distance and the growth of GaInP.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, domains of ordered GaInP are formed during the overgrowth, having a double periodicity in the ͓1 11͔ and ͓11 1͔ directions. 23 The QD-induced ordering for this particular material system has recently been discussed in detail in Refs. 16 and 23. There is a rather complex interplay between the QD-QD distance and the growth of GaInP.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the observed undulations have a larger horizontal lattice spacing in the ͓110͔ direction. [15][16][17] The degree of polarization for the QDs on the undulations ͑66%͒ is, however, higher than the 36%-45% for QDs without undulations. 9 This strain anisotropy can also directly cause an anisotropy in the polarization of the optical emission, independent of the structural morphology.…”
mentioning
confidence: 92%
“…The degrees of polarization are 46% for the InGaP buffer layer and 66% for the InP QDs, both from sample A. 15 If one of these properties is weak in the structure then the anisotropy is more pronounced in the opposite direction. 2͑a͒ and reflecting the influence the undulations have on the ͑-PL͒ polarization orientation.…”
mentioning
confidence: 98%
“…The tacit assumption throughout the vast majority of the international "quantum dot community" is that Stranski-Krastanow grown random alloy QDs are structurally stable. Recent experimental observations, however, seem to indicate that this is at least for several III-V, II-VI, and IV-VI compound semiconductor systems not the case [5][6][7][8][9][10][11][12]. In these systems it appears that it is atomically ordered or phase separated QDs that are structurally stable, i.e.…”
Section: Introductionmentioning
confidence: 99%